Efficient key distribution protocol for mobile devices in cloud environments - Su Jeong, Yoon; Tae Kim, Yong; Cheol Park, Gil (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, as the fourth industrial revolution has emerged, cloud computing services have been attracting attention for efficient use of Internet-based computing resources. Among the cloud computing services, even if the data processed by the mobile device is encrypted after being stored in the server, the confidential information can be leaked. Therefore, there is a need for the key generation for data encryption and decryption.Methods/Statistical analysis: In this paper, we propose a key distribution protocol that enables mobile devices to securely encrypt and decrypt keys in an efficient manner in a cloud environment. The main purpose of the proposed protocol is to maximize the efficiency and cost reduction of key generation, which can securely transmit and receive data, in a situation where the size of data used in the cloud environment and the storage location are increasing. As a result of the performance evaluation, the proposed method improved the authentication processing time by 4.1% on average compared with the existing protocol, and the average throughput rate of the server per unit time was 6.5%. In addition, the communication delay time between the authentication server and the mobile device improved by 9.3% on average, and the authentication overhead of the server was 11.5% lower than that of the conventional method.Findings: In order to solve this problem, the proposed protocol can solve the security problem of the mobile device because it can receive the authentication through the one - way hash function and the XOR operation using the encrypted data using the session key.Improvements/Applications: In future studies, we will apply the proposed protocol to the actual environment based on the results of this study and compare it with the results obtained from the theoretical studies.Â